New Mexico government and politics - Vigil, Maurilio E.; Olsen, Michael; Lujan, Roy (Lanham, Md. University Press of America, 1990)
This book provides a comprehensive and penetrating investigation of the governmental and political processes of New Mexico. It combines a view of how the social and political history have shaped contemporary New Mexico political culture and the nature of governmental and political affairs. Formal governmental institutions and political processes provide a descriptive narrative of New Mexico government and politics. Contents: PART I: The Function of State Government; The Land of Enchantment; Paso por aqui; Powers Not Delegated; Any Amendment or Amendments to this Constitution; PART II: The Form of Government; The Executive Department Shall Consist of...; The Legislative Power Shall Be Vested In; The Judicial Power of the State Shall Be Vested In; All Elections Shall be Free and Open: Parties and Politics in New Mexico; From Bernalillo to Valencia: County Government; From Aztec to Wagon Mound: Municipal Government; Pueblos, Acequias and Land Grants: Other Political Units Mexico; PART III: The Future of State Government; Public Policymaking in New Mexico.
81263
Keywords: New Mexico -- Politics and government -- 1951-